Magnetic Properties of Cobalt-coated Silicon Steels Prepared by Electrodeposition - PIROMRAK, Somkane; JANTARATANA, Pongsakorn; SIRISATHITKUL, Chitnarong (Walailak Journal of Science and Technology (WJST), 2011)
Magnetic properties of silicon steels (1.26 % silicon) coated by cobalt of varying thickness were studied. Cobalt ranging from 11 to 68 µm in thickness was deposited on silicon steel substrates (0.5 mm thick, 0.4 mm wide and 55.0 mm long) cut from sheets of recycled transformer cores. By electrodeposition in CoSO4 electrolyte with 90 mA applied current at pH 1.86, the deposition rate was 1.11 µm/min. Although deposition of cobalt increased saturation induction of silicon steels, it also increased hysteresis loss signified by wider hysteresis loops with larger remanent induction and coercive field. Since the magnetoimpedance (MI) is related to the magnetic softness of materials, the MI ratio decreased with increasing thickness of the cobalt layer. Although the cobalt coating did not enhance the MI ratio of silicon steels, it expanded the peak of frequency-dependent MI curves. Therefore, the frequency range with large MI ratio in silicon steels can be extended by the deposition of a cobalt layer. From microscopic images, grains and magnetic domains of the silicon steel were of the order of 10 µm whereas smaller domain size was observed in the cobalt layer.